Pharmaceutical and pharmacological studies of Shen Ma Yi Zhi granule for prevention of vascular dementia: A review - Chang, Su-rui; Liu, Jian-gang; Li, Hao; Liu, Mei-xia; Shi, Dan-dan; Zhou, Li-juan (Frontiers in Neuroscience, 2022)
Background: With dementia significantly increasing hospitalization and disability rates, worldwide aging of the population presents major challenges to public health. The majority of cases of cognitive dysfunction among the elderly, however, are characterized by an identifiable, preventable and treatable vascular component. As such, increased study of preventative methods in the context of dementia is warranted. Traditional Chinese medicine compounds have been reported to be neuroprotective and improve cognitive function via a variety of mechanisms. Shen Ma Yi Zhi granule (SMYZG) is one such collection of compounds that has been proven clinically effective. Pharmacological mechanisms of action, pharmacokinetics and clinical applications of SMYZG have been previously studied using a variety of vascular dementia animal models. SMYZG activates and regulates four main signaling pathways relevant to vascular dementia including the AMPK/PPARα/PGC-1α/UCP2, Nrf2/HO-1, HIF-1/VEGF/Notch, and VEGF/Flk-1/p8 MAPK pathways. Furthermore, SMYZG influences anti-inflammatory and anti-oxidant stress responses, reverses demyelination of brain white matter and vascular endothelium, regulates pericyte function and normalizes mitochondrial metabolism. Neuroprotective effects of SMYZG, as well as those promoting regeneration of vascular endothelium, have also been reported in studies of rat models of vascular dementia. Future research concerning SMYG is warranted for development of vascular dementia preventative management strategies.